POLITICAL IDEOLOGY AND IDEOLOGICAL DISCOURSE - Швирков, О.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
Today the concept of ideology is in the process of rethinking. On one hand there are reasons to give it up, on the other hand - to transform its content essentially. This article attempts to provide some new vision of ideology as well as to show that the ideology and ideological statements (ideological content) are absolutely different phenomenon and can not be reduced to one another.